Extreme vetting : a thriller - Arama, Roxana (Ooligan Press, 2022)
"Seattle, Washington, 2019. Attorney and single mom Laura Holban is an immigrant herself, guiding clients through a Kafkaesque system of ever-changing rules, where overworked judges make life-shattering decisions in minutes. Laura's newest client is Emilio Ramirez, who was arrested in front of his sons at their high school and thrown in detention. When Laura files for Emilio's asylum, the world turns upside down. False criminal charges prevent his release, someone is following his family, and an ICE prosecutor threatens to revoke Laura's US citizenship. None of it makes sense--until she uncovers a deadly conspiracy involving ICE, stolen data, and human trafficking. Now the man at the center of it all is coming after Laura and Emilio, who must find a way to survive--and keep their families safe"--